2014
DOI: 10.1177/0894845314544033
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Exploration of the STEM Career-Related Outcome Expectations of Young Adolescents

Abstract: Perceptions developed and choices made during the preadolescent and early adolescent years may restrict or enrich youth's future career aspirations. These years are critical for acquiring and exploring academic and career-related interests. In addition, outcome expectations -what youth believe will happen if they pursue certain interests, tasks, or goals -are important predictors of eventual career choice. With national, state, and local initiatives advocating science, technology, engineering, and mathematics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 29 publications
(78 reference statements)
6
33
0
1
Order By: Relevance
“…Lent et al [38] suggest that there are a number of theories which suggest that outcome expectation can play a key role in motivating behaviour. Advisers should be aware of negative expectations, because some of these expectations are often misguided, or illogical, and may influence students' choices [54]. In Kuwait, El-Bahey and Zeid [21] found that the most important factor influencing a decision to study CS to be career and future considerations.…”
Section: Outcome Expectationmentioning
confidence: 99%
“…Lent et al [38] suggest that there are a number of theories which suggest that outcome expectation can play a key role in motivating behaviour. Advisers should be aware of negative expectations, because some of these expectations are often misguided, or illogical, and may influence students' choices [54]. In Kuwait, El-Bahey and Zeid [21] found that the most important factor influencing a decision to study CS to be career and future considerations.…”
Section: Outcome Expectationmentioning
confidence: 99%
“…More research is needed to understand how youth organizing experiences in a variety of contexts support socially‐oriented career outcomes. Scholars have begun to apply Social Cognitive Career Theory (SCCT) to this aim exploring how youth consider outcomes beyond themselves, when making career decisions (Lent, Brown, & Hackett, ; Shoffner, Newsome, Minton, & Morris, ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have illustrated how outcome expectations are different for a particular demographic. For example, Schoffner and others () studied outcome expectations of young adolescents, and Hartman and Hartman () determined how outcome expectations in science, math, and engineering careers vary by gender. Recognizing the forces that shaped our own outcome expectations while also identifying the outcome expectations of our recruitment audience will help us connect them with careers that can help meet those expectations.…”
Section: Discussionmentioning
confidence: 99%